PARENTAL INVOLVEMENT IN THE EDUCATION OF CHILDREN WITH SPECIAL NEEDS: REVIEWING RELATED LITERATURE - Arbianingsih (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study reviews the literature related to parental involvement in the education of children with special needs and its impact on children's development. The results show that active parental involvement contributes significantly to the academic progress and social-emotional development of children with special needs. It also improves the overall quality of family life through a better understanding of children's needs and the creation of a supportive learning environment. However, there are several barriers that hinder parental involvement, such as lack of information and resources, and financial burden. Therefore, support from the government, schools and communities is needed to optimise parental participation in the education of children with special needs.